Unemployment in the Najran Region (Causes and Means of Overcoming It): A Jurisprudential and Social Study Within the Framework of the Kingdom of Saudi Arabia’s Vision 2030 - El-Sayed Abu El-Ala, Khaled Fouad; Al-Mansy, Mohammed Qasim (Journal of Neonatal Surgery, 2025)
Unemployment in the Najran region constitutes a major issue affecting residents of this area, both Saudi nationals and individuals of other nationalities. The unemployment rate among Saudis reached 6.4%, although it decreased to 5.8% in the third quarter of 2022, according to the General Authority for Statistics. Nevertheless, the problem remains persistent. This research identifies the principal causes of unemployment in the Najran region and highlights measures for overcoming it, through a jurisprudential and social study within the framework of the Kingdom of Saudi Arabia’s Vision 2030. Research Objectives included the following principal aims: Providing Sharia-based responses to questions related to unemployment. Identifying a set of causes for the problem of unemployment in the Najran region and the proposed solutions. Demonstrating the capacity of Islamic Sharia to offer appropriate solutions to contemporary issues faced by people in their daily lives. This research has concluded with a set of scientific findings detailed at its conclusion. It has also concluded with a set of important recommendations outlined at the end, which are relevant to the subject matter of this research